Influence of Environmental Values on Purchase Intention of Selected Personal Care Products Among Consumers - Atienza, Julius Paolo; Arturo, Mary Rose; Bautista, Antoinette; Bonguit, Pauline Gail (IJOSMAS, 2022)
Personal care products or PCPs are one of the emerging water contaminants and environmental pollutants in the world. These environmental concerns are opening the eyes of the consumers to adopt greener lifestyle practices and switch to more sustainable habits. The rising go-green consciousness has pushed industries handling personal care products to redefine sustainability. This study's primary objective is to examine Filipino non-green consumers’ purchase intention of personal care products, specifically, the PCP categories of dental and oral care, hair care, and skincare, based on their environmental values. Accordingly, we will further investigate how brand perception modifies purchase intentions of personal care products. The 397 qualified respondents used for the analysis are currently residing in the Greater Manila Area, which consists of Metro Manila and the nearby provinces of Cavite, Rizal, Laguna, and Bulacan. The preliminary reliability results generated from the pilot test showed that Cronbach’s alpha values for all constructs exceeded the acceptable value of 0.7. The study used Pearson’s product-moment correlation coefficient, and multiple regression analysis to measure the relationships of the variable. The results provide a better understanding of how environmental values and characteristics of these non-green consumers can help businesses enhance how they should cater to this type of consumers, which, in turn, can help improve brand performance.